Peningkatan Hasil Belajar dan Pemahaman Siswa dengan Menggunakan Metode Praktek pada Materi Jenis Bumbu Dasar dan Pengembangannya - Ikhwanul Badariah (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
The learning process for basic spices and their development in basic culinary lessons in class X Catering at SMK N 3 Karang Baru is still poorly understood, so that student activity in class is still lacking. This has an effect on the low score obtained by students, namely 63.57 with a KKM of 75. The steps taken to overcome this are by using suitable and interesting learning methods so that learning outcomes and students' understanding of learning increase. The application of practical learning methods is one of the researchers' efforts to improve student learning outcomes and understanding of student learning. The research was carried out in 2 cycles. Each cycle consists of stages of planning, implementation, observation, and reflection. The research data includes student learning outcomes taken from giving test questions at the end of the cycle, on the teacher's ability in learning from observation sheets, and data on student reflection on learning from student responses at the end of the cycle. The indicators of research success are: (1) if 80% of the total number of students are categorized as complete, (2) if the teacher's performance ability is at least in good category, (3) if students are categorized as having high interest/interest in the learning provided. The results showed that the understanding of student learning outcomes increased, namely in the first cycle 70.71 and in the second cycle 95.23, the teacher's performance ability was categorized as very good, and students' interest in the learning provided by the teacher was in the high category, students liked the teacher and practical learning methods.